2001
DOI: 10.1103/physrevb.63.165321
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and vertical transport in random dimerGaAsAlxGa1x

Abstract: We report a systematic study of several GaAs-Al x Ga 1Ϫx As semiconductor superlattices grown by molecular-beam epitaxy specifically designed to explore the existence of extended states in random dimer superlattices. We have confirmed our previous results ͓V. Bellani et al., Phys. Rev. Lett. 82, 2159 ͑1999͔͒ with much additional evidence that allows us to lay claim to a clear-cut experimental verification of the presence of extended states in random dimer superlattices due to the short-range correlations ͑dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
10
1
Order By: Relevance
“…This feature opened the possibility to verify experimentally former theoretical predictions, such as Stark-Wannier ladders, 1 Bloch oscillations, 2 Anderson localization by uncorrelated disorder, 3 and electron delocalization by correlations in the disorder. 4 Concerning this last finding, photoluminescence ͑PL͒ and electron-transport experiments in intentionally disordered SL's showed that spatial correlations of the disorder lead to electron delocalization of states in low-dimensional systems, 4,5 as previous theoretical calculations suggested, 6 in contrast to the earlier belief that all eigenstates might be localized. This is a validation of basic physical phenomena, i.e., the inhibition of Anderson localization in quasi-one-dimensional systems with correlated disorder, predicted theoretically at the beginning of the 1990's.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…This feature opened the possibility to verify experimentally former theoretical predictions, such as Stark-Wannier ladders, 1 Bloch oscillations, 2 Anderson localization by uncorrelated disorder, 3 and electron delocalization by correlations in the disorder. 4 Concerning this last finding, photoluminescence ͑PL͒ and electron-transport experiments in intentionally disordered SL's showed that spatial correlations of the disorder lead to electron delocalization of states in low-dimensional systems, 4,5 as previous theoretical calculations suggested, 6 in contrast to the earlier belief that all eigenstates might be localized. This is a validation of basic physical phenomena, i.e., the inhibition of Anderson localization in quasi-one-dimensional systems with correlated disorder, predicted theoretically at the beginning of the 1990's.…”
contrasting
confidence: 48%
“…4 -6 The OSL and DSL present band of extended states while in the RSL all the states are localized, as theory 6 and experiments showed. 4,5 Therefore, the arrangement of electronic levels responsible for the optical transitions depends on the SL considered ͑OSL, RSL, or DSL͒.…”
mentioning
confidence: 99%
“…Additional details on the samples can be found in previous publications. 3,20 Our previous theoretical and experimental results 3,20,21 showed that whereas in the RSL the states are localized, the DSL supports a narrow band of critical ͑non-Bloch-like͒ extended states, while the OSL supports a wide band of Bloch extended states. Therefore, in the OSL the carriers are mobile either in the growth direction or in the plane.…”
Section: Methodsmentioning
confidence: 96%
“…Now we turn to the calculation of the galvanomagnetic tensor component. One finds components for the generalized impulse P when the electric field is directed parallel to the x-axis and the magnetic field, normal to the electrical field, is parallel to the y-axis (E ¼ E x , H ¼ H y ) and incorporates expressions in the non-equilibrium distribution function, equation (2). Then, substituting the expressions in the current density formula…”
Section: Solution Of the Kinetic Equation And Galvanomagnetic Tensormentioning
confidence: 99%
“…However, it was recently discovered that the systems also possess fascinating transport properties in the range of non-quantizing magnetic fields. Among these properties is the Hall effect in a quasi-two-dimensional electron gas in weak magnetic fields [1][2][3][4]. The Hall coefficient in layered crystals and superlattices, where an electron gas is quasitwo-dimensional, substantially depends on the mutual arrangement of the electric and magnetic fields and the axis normal to the layer plane.…”
Section: Introductionmentioning
confidence: 99%